Knowledge and attitudes about mental disorder amongst media practitioners in Southwest Nigeria - Oluwole, Lateef O.; Obadeji, Adetunji (International Journal Of Community Medicine And Public Health, 2017)
Background: The mass media, described as the most important source of information about mental health issues, touch all aspects of everyday live. Media professionals remain a potent and unique factor in conveying positive messages about mental health that educate the public. This study sought to assess knowledge and attitudes about mental disorders amongst the media practitioners. Methods: Study population consists of media practitioners in a southwest Nigerian city. The World psychiatric association questionnaire measuring attitudes towards schizophrenia was modified and administered to the study group. Results: Some socio-demographic factors including years of experience and educational attainment were significantly related to attitudes shown by this group of professionals towards people with mental disorder. Conclusions: Consequent expression of negative attitudes by media practitioners towards the mentally ill suggests a need for educational program be organized for media practitioners to change their misconceptions about mental disorder and the mentally ill.